An empirical study of e-learning initiative in modern electronic industries - Annusia , Ramasamy (2005)
The famous riddle in the training and development fraternity is: What do some training and development professionals view as both an opportunity and a threat? The answer: e-learning. While some trainers view it as preying upon their insecurities, others understand that e-learning is a tool to help learners gain a comprehensive knowledge of a specified field - an elusive task due to rapid product development and evolution. However, far at large there are still doubts on a full-blown e-learning initiative company wide. Why and what should we do about it, is my next course of action. The purpose of this study was to identify some determinants that initiate elearning motivation modern industries. The study examines the independent variables which were the organizations demography, IT infrastructures, cost of implementation, learning culture and KSAO of the course content developers linking the relationship of moderating variables; influence and exploration from the government and e-learning fraternity and the identification of LMS, to the dependent variable - e-learning initiatives. Data were collected from a sample of 103 organizations in the state of Penang Island, west peninsular Malaysia. The findings in general provide support to the hypothesis formulated. The results showed that the relationship among KSAO of content developers, IT infrastructure, cost of implementation and the learning culture were fully supported by the analysis. Master of IT- Open University Of Malaysia An empirical study of E-Learning Initiatives in modern organization. This study has essential implication for organizations. Managements have to first understand what initiate the motivation of implementing e-learning in the organizations for the global challenges in order to stay competitive in today's challenging learning, training and development environment. (Author's abstract)